Mekanisme Penyelesaian Sengketa Dalam Perdagangan Berjangka Komoditi - I Nengah Mahendra Adi Sanjaya; Deli Bunga Saravistha (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
Commodity futures trading is everything related to the sale and purchase of commodities with margin withdrawals and later settlement based on futures contracts, sharia derivative contracts, and/or other derivative contracts. Commodities are all goods, services, rights and other interests, and any derivatives of commodities, which can be traded and become the subject of futures contracts, sharia derivative contracts, and/or other derivative contracts. The purpose of this study is to find out what is meant by commodity trading and dispute resolution mechanisms in commodity futures trading either in an alternative or litigation manner. This study also explains the law concerned with commodity futures trading. This study uses normative research methods. Normative legal research is legal research conducted by examining literature or secondary data